Profil mi islamiyah kalipucang kulon dalam upaya meningkatkan kepercayaan orang tua melalui prestasi akademik dan non-akademik - Salisa Dina Sakinah; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2025)
. This study aims to (1) analyze the efforts made by MI Kalipucang Kulon in increasing parental trust through the management and achievement of student academic achievement, (2) identify MI Kalipucang Kulon's strategies in increasing parental trust through the management and achievement of student non-academic achievement, and (3) reveal the obstacles faced by MI Kalipucang Kulon in increasing parental trust and providing relevant solutions to overcome these obstacles. The study was conducted at MI Kalipucang Kulon using a qualitative phenomenological approach. Data were collected through observation, interviews, and documentation. The results of the study showed that academic activities such as remedial and academic competitions, as well as non-academic activities such as drum bands, had a significant effect on parental trust. Obstacles such as miscommunication were overcome with effective communication and transparency. It was concluded that academic and non-academic activities play an important role in building parental trust. These findings provide a basis for developing strategies to increase parental trust in madrasahs.